Computer Applications for Database, Education and Ubiquitous Computing International Conferences, EL, DTA and UNESST 2012, Held as Part of the Future Generation Information Technology Conference, FGIT 2012, Gangneug, Korea, December 16-19, 2012. Proceedings - Kim, Tai-hoon; Ma, Jianhua; Fang, Wai-chi; Zhang, Yanchun; Cuzzocrea, Alfredo (Communications in Computer and Information Science, 2012)
This volume constitutes the refereed proceedings of the International Conferences, EL, DTA and UNESST 2012, held as part of the Future Generation Information Technology Conference, FGIT 2012, Kangwondo, Korea, in December 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of education and learning, database theory and application and u- and e-service, science and technology.